Pengembangan Bisnis Media The Jakarta Post Digital - Dandy Indriawijaya Koswaraputra; Bonar M. Sinaga; Trias Andati (School of Business, Bogor Agricultural University (SB-IPB), 2019)
This research aimed to identify the existing business model implemented by The Jakarta Post Digital by using Business Model Canvas (BMC) approach in order to create a new business model after being analyzed by the SWOT method. The results of the analysis showed that the company's strength is on Key Resources and its weaknesses are on Key Activities and Value Proposition. Based on the results, it is necessary to improve the nine elements of the Business Canvas Model, especially for the three blocks. Therefore, this research concluded that there is a need for improvement in the business model of The Jakarta Post Digital on Value Proposition block by improving Multimedia products, such as infographic and short videos. The Key Activities block also need to be changed by focusing on multimedia development. The Key Resources need to be improved; including the studio, multimedia equipment and human resources. Therefore, the production process becomes more efficient, and the quality and quantity of the outputs are increasing, which implicate in the change of Revenue Stream.Keywords: digital, media, business model canvas, SWOT, the jakarta postAbstrak: Tujuan penelitian ini adalah untuk mengidentifikasi model bisnis yang saat ini digunakan oleh The Jakarta Post Digital dengan menggunakan pendekatan Business Model Canvas (BMC) untuk kemudian menciptakan model bisnis baru atau perbaikan setelah dianalisis dengan metode SWOT. Hasil analisis menunjukkan bahwa kekuatan perseroan ada pada sumber daya kunci (Key Resources) dan kelemahannya ada pada kegiatan produksi (key activities) dan produk atau jasa yang ditawarkan (value proposition). Hasil idenfikasi tersebut, maka diperlukan perbaikan pada kesembilan elemen yang terdapat pada model bisnis kanvas terutama pada 3 blok tersebut. Dengan demikian, penelitian menyimpulkan perlu adanya perbaikan pada model bisnis The Jakarta Post Digital pada blok value proposition, yaitu dengan meningkatkan produk Multimedia. Pada blok key activities juga mengalami perubahan dengan penambahan fokus pada pengembangan multimedia. Selain itu, key resources juga diperbaiki pembangunan studio beserta peralatan penunjang produksi multimedia, termasuk SDM. Dengan demikian, proses produksi menjadi lebih efisien yang berimplikasi pada perubahan revenue stream.Kata kunci: digital, media, business model canvas, SWOT, the jakarta post